(untitled) (Indian Journal of Public Health Research & Development, 2020)
The main objective of the study was to explore the factor of happiness among the adolescent’s students the other objective was to formulate the theoretical structure of the happiness for the adolescent’s population of Chhattisgarh India. For these purpose 250 adolescents studying in different schools of Chhattisgarh constituted the sample for the study. The students were asked to give an open-ended answer to a question “what makes them happy” analysis was performed for their responses 28 common responses after analyzing the responses were identified. A hypothetical exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) was computed to find out the factors of happiness among adolescents. The results of the EFA revealed 5 factors of happiness for adolescents. The results of CFA reveal a low correlation between the 5 factors